Association between maternal weight gain during pregnancy and child’s body mass index at preschool age - Jeewon Shin; Yoowon Kwon; Ju Hee Kim; Su Jin Jeong (Clinical and Experimental Pediatrics, 2023)
Background Recent studies reported that prepregnancy body mass index (BMI) and weight gain during pregnancy affect birth weight and contribute to childhood obesity. However, no such data are available in Korea. Purpose This study gathered data on weight gain during pregnancy and its impact on birth weight and childhood obesity in Korea. Methods We reviewed 1,753 singleton full-term babies born at CHA Bundang Medical Center in 2014–2016. We first review each maternal and baby factor based on prepregnancy BMI (underweight, normal, overweight/obese) and then divided them into low, normal, and excess gestational weight gain (GWG) groups based on the American Institute of Medicine (IOM) guidelines. We reviewed the characteristics of each group and analyzed the association between maternal GWG based on IOM guidelines and child BMI after 6 years. Results The maternal prepregnancy BMI group showed a significant difference in birth weight and child BMI at 6 years. As the prepregnancy BMI increased, the birth weight and BMI at 6 years also increased (P<0.001). Mean birth weight and child BMI at 6 years differed significantly among the GWG groups. Furthermore, excess postpartum weight gain increased the risk of childhood overweight and obesity (odds ratio, 2.21; 95% confidence interval, 1.40–3.49). Conclusion Excess weight gain during pregnancy should be avoided due to its short- and long-term association with childhood obesity. Owing to the high prevalence of excess GWG and childhood obesity, excess weight gain during pregnancy can have significant public health implications.